EZH1/2 dual inhibitors suppress HTLV-1-infected cell proliferation and hyperimmune response in HTLV-1-associated myelopathy - Koseki, Akihito; Araya, Natsumi; Yamagishi, Makoto; Yamauchi, Junji; Yagishita, Naoko; Takao, Naoki; Takahashi, Katsunori; Kunitomo, Yasuo; Honma, Daisuke; Araki, Kazushi; Uchimaru, Kaoru; Sato, Tomoo; et al. (Frontiers in Microbiology, 2023)
Background: Human T-cell leukemia virus type 1 (HTLV-1) causes HTLV-1-associated myelopathy (HAM), adult T-cell leukemia/lymphoma (ATL), HTLV-1-associated uveitis, and pulmonary diseases. Although both HAM and ATL show proliferation of infected cells, their pathogeneses are quite different. In particular, the pathogenesis of HAM is characterized by hyperimmune responses to HTLV-1-infected cells. Recently, we demonstrated the overexpression of histone methyltransferase EZH2 in ATL cells and the cytotoxic effects of EZH2 inhibitors and EZH1/2 dual inhibitors on these cells. However, these phenomena have never been studied in HAM. Furthermore, what effect these agents have on the hyperimmune response seen in HAM is completely unknown. Methods: In this study, we investigated histone methyltransferase expression levels in infected cell populations (CD4+ and CD4+CCR4+ cells) from patients with HAM using microarray and RT-qPCR analyses. Next, using an assay system that utilizes the spontaneous proliferation characteristic of peripheral blood mononuclear cells derived from patients with HAM (HAM-PBMCs), we investigated the effects of EZH2 selective inhibitors (GSK126 and tazemetostat) and EZH1/2 dual inhibitors (OR-S1 and valemetostat, also known as DS-3201), particularly on cell proliferation rate, cytokine production, and HTLV-1 proviral load. We also examined the effect of EZH1/2 inhibitors on the proliferation of HTLV-1-infected cell lines (HCT-4 and HCT-5) derived from patients with HAM. Results: We found elevated expression of EZH2 in CD4+ and CD4+CCR4+ cells from patients with HAM. EZH2 selective inhibitors and EZH1/2 inhibitors significantly inhibited spontaneous proliferation of HAM-PBMC in a concentration-dependent manner. The effect was greater with EZH1/2 inhibitors. EZH1/2 inhibitors also reduced the frequencies of Ki67+ CD4+ T cells and Ki67+ CD8+ T cells. Furthermore, they reduced HTLV-1 proviral loads and increased IL-10 levels in culture supernatants but did not alter IFN-γ and TNF-α levels. These agents also caused a concentration-dependent inhibition of the proliferation of HTLV-1-infected cell lines derived from patients with HAM and increased annexin-V(+)7-aminoactinomycin D(-) early apoptotic cells. Conclusion: This study showed that EZH1/2 inhibitors suppress HTLV-1-infected cell proliferation through apoptosis and the hyperimmune response in HAM. This indicates that EZH1/2 inhibitors may be effective in treating HAM.